Determination of DMS and other volatile compounds in beer by headspace capillary gas chromatography and flame ionisation detection: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Dupire, S. (BrewingScience, 2000)
The determination of beer volatiles by the headspace capillary gas chromatography with flame ionisation detection method of the Institute of Brewing Analysis Committee has been collaboratively tested by the members of the Analysis Committee of the European Brewery Convention and some members of the American Society of Brewing Chemists. Determined analytes were acetaldehyde, dimethylsulphide, ethylacetate, n-propanol, isobutanol, isoamylalcohols and isoamylacetates. The internal standards used were ethylmethyl sulphide and n-butanol. After three preliminary collaborative trials, a last fourth one was performed on three beer samples in 15 laboratories. Repeatability (r₉₅) and reproducibility (R₉₅) values were obtained for 12 laboratories. Assuming that too many members did not follow exactly the proposed method and judging that reproducibility values were poor, it was decided to not include the method in the Analytica EBC as an official method, but to include it as a guideline method with the aforementioned notice.